A Double-Blind, Randomized, Active Drug Comparative, Parallel-Group, Multi-Center Clinical Study to Evaluate the Safety and Efficacy of Probiotics (, Zhengchangsheng® capsule) in Patients with Diarrhea - Jun Heo; Sung Kook Kim; Kyung Sik Park; Hye Kyung Jung; Joong Goo Kwon; Byung Ik Jang (Intestinal Research, 2014)
Background/AimsBacillus Licheniformis, a probiotic used in the treatment of diarrhea, has been shown to suppress the growth of pathologic bacteria. This study was performed to assess the therapeutic efficacy and safety of Zhengchangsheng® (Bacillus Licheniformis) in comparison with another probiotic, Bioflor® (Saccharomyces Boulardii) for the treatment of diarrhea.MethodsPatients with diarrhea (n=158) were randomized to receive Zhengchangsheng® or Bioflor® for 5 days. The existence or non-existence of formed feces, changes in daily stool frequency, improvement of subjective symptoms, and changes in the severity of diarrhea were compared.ResultsOf the 158 full analysis set (FAS) patient population, 151 patients comprised the per protocol (PP) analysis. The rates of recovered to formed feces in the Bacillus and Saccharomyces groups were 91.0% vs. 95.0% in the FAS (P=0.326) and 90.5% vs. 96.1% in the PP analysis (P=0.169), respectively. The mean duration of diarrhea changing to formed feces was 3.15±1.10 days in the Bacillus group and 3.22±1.01 in the Saccharomyces group (P=0.695, FAS). The frequency of defecation, subjective symptoms, and degree of severe diarrhea were improved in both groups, however, there were no statistically significant differences between the 2 groups. Analysis of the 95% confidence intervals for the differences in the rate of recovery to formed feces between the 2 groups met the criteria for non-inferiority of Bacillus compared to Saccharomyces. No significant adverse events were observed during the study period.ConclusionsZhengchangsheng® is not inferior to Bioflor® in therapeutic efficacy and is a safe and useful therapeutic agent for the treatment of diarrhea.